Research on the adaptability of packers for integrated string fracturing operations in low porosity and low permeability reservoirs - Wang, Zhiyong (Strojniški vestnik, 2024)
To study the failure of conventional packers in the fracturing and stimulation of low-porosity and low-permeability reservoirs and reduce the failure accidents of packers in the fracturing process, a suitable integrated string packers was selected in the process of fracturing and stimulation in an oilfield in the Middle East as a case study. Three different well types have been established. The wellbore temperature distribution and the axial force of the string can be calculated under the conditions of various wellhead pressures and different displacement, and it is found that the temperature at the bottom of the well can reach 130 °C, and the maximum axial force at the wellhead is 500 kN. At the same time, the applicability of retrievable tubing testing squeeze (RTTS) and hydraulic-set retrievable (RH) packer in different working conditions was evaluated, and it was found that only RTTS packers can meet the needs of the oil field. According to the calculated temperature field and axial force distribution, the stress on different components of the packer under different working conditions is established during the fracturing-stimulation operation. In the worst working conditions, the maximum stress of the packer occurs at the lower part of the central pipe, reaching 303.83 MPa, which is in a safe state. The contact stress on rubber rings can reach 30 MPa, indicating that the sealing performance can meet the requirements of on-site use. The temperature and axial force data calculated by the model provide a theoretical basis for safe well control. Through model evaluation, it was found that the RTTS packer can be suitable for the fracturing and stimulation needs of the oilfield. The research methods and achievements in the article provide theoretical guidance for evaluating the applicability of packers in the fracturing and stimulation process of low porosity and low permeability reservoirs.
Keywords: acid fracturing; finite element simulation; gumijast obroči; integrated pipe string; integrirana kolona cevi; lomljenje s kislino; low porosity and low permeability reservoirs; metoda končnih elementov; nahajališča z nizko permeabilnostjo; nahajališča z nizko poroznostjo; packer rubber ring; simulacije